Akuntabilitas Pengelolaan Anggaran pada Komisi Pemilihan Umum (KPU) Kota Cilegon - Zainuri, Ahmad (Universitas Serang Raya, 2018)
Good or not the services of government agencies can be measured through the implementation of Good Governance principle in the agency. One of the characteristics of Good Governance is accountability. This research aimed to examine the implementation of budget management accountability at Cilegon City Election Commision (KPU). This research employed a descriptive qualitative method. The data were collected through interviews, observations and document reviews. The analysis results showed that Cilegon City KPU still did not apply the good budget management accountability for example some procurement of goods and services and other facilities did not have clear evidence of transactions and some of them were unrealistic and did not correspond to the market price. Based on the research results, it is recommended that regular training ought to be conducted to develop the skills of budget administrators both of the Commission and the PPK and PPS. The Commission together with the Chairmen of the PPK and PPS needs to monitor the implementation of the budget in the field. The Commission should involve all stakeholders to discuss the budget accountability report.